Révolution et recherche : développement durable et transformations sociales à Cuba - Sabrina Doyon (EchoGéo)
Education is one of Cuba’s revolutionary milestones. It contributes to the country’s international notoriety as well as it is central to the revolutionary identity. This sector is now under important economic pressures threatening the Revolution’s future. Based on ethnographic data, this paper analyses the individual and institutional implications of foreign capital investments in a local research project funded by an international aid organization in the contemporary “post-Castro” era.